2016
DOI: 10.1021/acs.molpharmaceut.6b00586
|View full text |Cite
|
Sign up to set email alerts
|

Brain Targeting of Temozolomide via the Intranasal Route Using Lipid-Based Nanoparticles: Brain Pharmacokinetic and Scintigraphic Analyses

Abstract: The aim of the present work was to investigate the efficacy of temozolomide nanostructured lipid carriers (TMZ-NLCs) to enhance brain targeting via nasal route administration. The formulation was optimized by applying a four-factor, three-level Box-Behnken design. The developed formulations and the functional relationships between their independent and dependent variables were observed. The independent variables used in the formulation were gelucire (X), liquid lipid/total lipid (X), Tween 80 (X), and sonicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…The results showed that intranasal administration of TMZ‐NLCs in rats was efficient to maintain the effect of TMZ with higher brain concentrations owing to direct brain targeting and increased residence time of the drug in the brain as compared with intranasal TMZ dispersion. These results illustrate the potential of the nose‐to‐brain delivery route for nanoparticles for the treatment of brain tumors (Khan et al, ). Nevertheless, during pharmaceutical development, it is essential to use an adequate methodology for drug determination in analytical or bioanalytical assays, with an accurate quantification of the compounds of interest (Baptista, Oliveira, & Ferreira, ; Yazbi, Hassan, Khamis, Ragab, & Hamdy, ).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results showed that intranasal administration of TMZ‐NLCs in rats was efficient to maintain the effect of TMZ with higher brain concentrations owing to direct brain targeting and increased residence time of the drug in the brain as compared with intranasal TMZ dispersion. These results illustrate the potential of the nose‐to‐brain delivery route for nanoparticles for the treatment of brain tumors (Khan et al, ). Nevertheless, during pharmaceutical development, it is essential to use an adequate methodology for drug determination in analytical or bioanalytical assays, with an accurate quantification of the compounds of interest (Baptista, Oliveira, & Ferreira, ; Yazbi, Hassan, Khamis, Ragab, & Hamdy, ).…”
Section: Introductionsupporting
confidence: 63%
“…However, there are some drawbacks that compromise TMZ treatment efficacy, such as its short half‐life (Ostermann et al, ). This requires the administration of high systemic doses to achieve therapeutic levels in the brain, leading to side effects such as headaches, nausea, bone marrow depression, oral ulcerations and even aplastic anemia (Khan et al, ; Trinh et al, ). As an alternative to new therapies, the nasal route can be considered for TMZ delivery to the CNS, thereby avoiding the interference of first pass metabolism; additionally, this is an easy and non‐invasive route of administration, contributing to patient adherence and high‐efficiency treatment (Bahadur & Pathak, ; Fonseca et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is used as an oral cytotoxic agent for adjuvant chemotherapy in malignant primary brain tumors such as glioblastoma (Stupp et al, 2005) and malignant glioma (glioblastoma multiforme and anaplastic astrocytoma) (Brada et al, 1999;Marchesi et al, 2007). The drug contains an imidazole group connected to a tetrazole ring ( Figure 1) (Khan et al, 2016). Due to its relatively high cytotoxicity for cancer cells, TMZ is commonly preferred by clinicians (Payne, Pratap, Middleton, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The observed higher flux may be attributed to the presence of permeation enhancing surfactants in ZRS-NLC. Moreover, the relatively higher lipophilicity of ZRS allows significantly better permeation through the nasal mucosa [30].…”
Section: Cumulative Drug Permeation Measurements Via Ex-vivo Diffusiomentioning
confidence: 99%